PENGETAHUAN MAHASISWA DIII KEBIDANAN STIKES SANTA ELISABETH MEDAN TENTANG KELENGKAPAN PENCATATAN REKAM MEDIS - Rani Gartika Holivia Silalahi; Ermawaty Arisandi Siallagan (STIKes Santa Elisabeth Medan, 2018)
Hospitals as one of the health care facilities are required to make medical records. Medical records are written evidence of services provided by doctors that contain patient identity, examination, treatment, other actions and services that have been given to patients. Midwives as medical personnel who also provide health services have an obligation to make documentation of their midwifery care actions. Aim: This study aimed to analyze the relationship of midwifery DIII student knowledge about medical records with the completeness of filling in midwifery care documentation. Methode: This research was an analytic observational study with cross sectional design. The study population was all third level midwifery DIII students who served at Santa Elisabeth Hospital in Medan and were directly involved in filling in medical records. Data was obtained by observed the completeness of filling nursing care documentation in the medical record for the period August 1st-31st, 2018 and used a questionnaire to assess the level of knowledge of midwifery students about medical records (procedures for filling and legal aspects). Statistical test using Chi Square test. Result: In this study found significant results between variables of knowledge about the legal aspects of medical records (p = 0.011), procedures for filling nursing care documentation (p = 0.001). Variables of knowledge about medical records get significant results, namely (p = 0.004). Conclusion: There were a meaningful relationship between the knowledge of Midwifery DIII students about medical records with the completeness of filling in midwifery care documentation. Keywords: Students of DIII Midwifery, Knowledge, Medical Records, Midwifery Care Documentation.